Features of the work of large-span beam structures - A. K. Yusupov; H. M. Muselemov; R. I. Vishtalov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. This article discusses flat large-span structures, provides features of their work, as well as design examples. Formulas are given for determining the general dimensions of these structures.Method. Features of work and design, as well as calculation formulas are given. Shipping marks, types of sections and junctions of elements are given. A technique is described that allows to reduce span bending moments. Examples of rational design of beam trusses are given.Result. The given structural diagrams, as well as the analysis of their work, allow us to design long-span flat structures that are reliable, lightweight, technologically advanced in terms of manufacturing, transportation and installation. The types of sections and junctions described in the article are used in the practice of design and construction.Conclusion. The article discusses rational design solutions that allow reducing the own weight of flat large-span structures due to the optimal choice of their design and design scheme.